Justification the choice of import substitution strategy direction on maching building enterprises - Шипуліна, Юлія Сергіївна; Ващенко, Тетяна Володимирівна (Technology audit and production reserves, 2015)
Mechanical engineering is a very important sector for Ukraine budget formation. But in recent years the national producers lose the volume of internal market. It is connected with the low competitiveness of enterprises. The negative influence of outside factors, outdated manufacturing equipment and inefficient management system determine the position of producers in the industry. Therefore, the issue of import substitution becomes urgent with each year. In this article, the authors propose a scientific organization and economic scheme of a process control strategy of import substitution at the enterprise. Based on the efficiency analysis of company product policy the stages of analyzing of the suitability of implementing the strategy of import substitution are proposed. Economic analysis allows to determine the most advantageous direction of implementing the strategy of import substitution. In order to increase competitiveness in internal and foreign markets product policy and enterprise as a whole has to be effectively managed. The result of this article is a defined direction and product group for implementation of the import substitution strategy.